Real Lithuanian economic growth forecasting using artificial neural networks - Jakaitienė, Audronė; Tamošiūnaitė, Minija (Lietuvos matematikos rinkinys, 2003)
Methods for forecasting of Lithuanian gross domestic product (GDP) are analyzed. Prognoses obtained by means of linear models and artificial neural networks are compared.